(untitled) (Research, Society and Development, 2021)
The pandemic caused by the SARS-CoV-2 coronavirus, in addition to possibly causing alveolar lung injury and acute respiratory failure, has a high prevalence of cardiovascular diseases, especially venous thromboembolism (VTE). The work aims to expose, through the analysis of scientific articles, the main complications of the development of thrombosis in patients infected with COVID-19. This is a literature review of a qualitative nature based on scientific production based on studies already published between the years 2019 to 2021. Some studies suggest that patients with COVID-19 may present a state of hypercoagulability, in which a state of hypercoagulability occurs. increased serum factor VIII, von Willebrand factor and fibrinogen levels. Hypercoagulability may influence the development of deep venous thrombosis of the lower limbs and/or pulmonary embolism in these patients. SARS-Cov-2 infection presents with a variety of complications, with frequent reports of cardiovascular problems and the presence of a prothrombotic state, caused by mechanisms that have not yet been fully elucidated. The evidence about COVID-19 and its interaction with the coagulation and platelet activation system is not yet fully understood.